Self-Compassion Dengan Emotional Quotient Pada Masa Dewasa Awal - Rachmatika, Camelia; Lestari, Rr. Hesti Setyodyah (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2026)
Early adulthood is the stage when individuals experience various physical, psychological, social, and emotional changes that can affect their emotional well-being. Self-Compassion is the skill of treating oneself with understanding, kindness, and patience when faced with difficulties, failures or suffering. These findings highlight the importance of a positive attitude towards oneself in the development of healthy emotional intelligence. Additionally, several studies reveal that self-compassion can be an important mediating factor in influencing the development of one's emotional intelligence. The research method is quantitative with the type of research used is quantitative correlation to measure the relationship between two variables, namely regarding whether there is a correlation between variable X and variable Y. Thus, this study will try to describe the relationship between variables and determine whether there is a causal correlation between Self-Compassion and Emotional Quotient in early adulthood. According to the results of the product moment correlation test analysis assisted by the SPSS 29 for Windows application, it is known that the sig value is 0.001 <0.05 N 67 where the sig value <0.05, meaning that there is a significant positive correlation between Self-Compassion and Emotional Quotient, meaning that the higher the Self-Compassion, the higher the level of Emotional Quotient or (emotional intelligence). Based on the results of the correlation test analysis, the correlation level (R value) is 0.456. Based on the acquisition of the coefficient of determination (R square) of 0.208, which means that there is a correlation between variable X and variable Y. Where the calculation of R2 = 0.208 is around 0.456 or 45.6%. So the correlation value (R) is 45.6%, this value indicates a moderate correlation level. This research shows that individuals with good Self-Compassion tend to be better at recognizing and managing emotions, both their own and other people's emotions. So, in conclusion, Self-Compassion is very important for our well-being in early adulthood. It helps us feel happier, have better relationships with others, and be stronger when facing life's challenges. Keywords: Self-Compassion, Emotional Quotient